A Bibliometric Review of Open Innovation: Setting a Research Agenda. Issue 6 (2nd March 2016) - Randhawa, Krithika; Wilden, Ralf; Hohberger, Jan
Abstract : Through an objective, systematic, and comprehensive review of the literature on open innovation (OI), this article identifies gaps in existing research, and provides recommendations on how hitherto unused or underused organizational, management, and marketing theories can be applied to advance the field. This study adopts a novel approach by combining two complementary bibliometric methods of co‐citation analysis and text mining of 321 journal articles on OI that enables a robust empirical analysis of the intellectual streams and key concepts underpinning OI. Results reveal that researchers do not sufficiently draw on theoretical perspectives external to the field to examine multiple facets of OI. Research also seems confined to innovation‐specific journals with its focus restricted to a select few OI issues, thereby exerting limited influence on the wider business community. This study reveals three distinct areas within OI research: (1) firm‐centric aspects of OI, (2) management of OI networks, and (3) role of users and communities in OI. Thus far, studies have predominantly investigated the firm‐centric aspects of OI, with a particular focus on the role of knowledge, technology, and R&D from the innovating firm's perspective, while the other two areas remain relatively under‐researched. Further gaps in the literature emerge that present avenues for future research, namely to: (1) develop a more comprehensive understanding of OI by including diverse perspectives (users, networks, and communities), (2) direct increased attention to OI strategy formulation and implementation, and (3) enhance focus on customer co‐creation and conceptualize "open service innovation." Marketing (e.g., service‐dominant logic), organizational behavior (e.g., communities of practice), and management (e.g., dynamic capabilities) offer suitable theoretical lenses and/or concepts to address these gaps.